Cholesterol synthesis is required for cutaneous barrier function in mice. - Feingold, K R (1990)
Previous studies have shown that topical acetone treatment results in the removal of stratum corneum lipids and disruption of the permeability barrier. This disruption stimulates epidermal lipid synthesis which is associated with the rapid restoration of stratum corneum lipids and barrier function. The aim of this study was to determine the role of cutaneous cholesterol synthesis in the barrier recovery. Here we show that topical lovastatin, a competitive inhibitor of HMG CoA reductase, inhibits cholesterol synthesis. After acetone disruption of the barrier, the normal rapid return of cholesterol to the stratum corneum and recovery of barrier function is impaired in animals treated topically with lovastatin. When lovastatin animals are simultaneously treated topically with either mevalonate, the immediate product of HMG CoA reductase, or cholesterol, the final end product of the pathway, the recovery of the barrier is normalized. Lovastatin resulted in the delayed secretion and abnormal appearance of lamellar bodies. These results provide the first evidence demonstrating that cholesterol synthesis is required for the maintenance of barrier structure and function and suggests a crucial role for cholesterol synthesis in allowing for terrestrial existence.